Perception and preferences of teaching and learning methods among second year medical students: a cross sectional survey in a rural tertiary care teaching hospital - G., Manu; S., Padmanabha T.; T, Chandrakantha; K, Neha (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Imparting a large amount of knowledge within a limited time period in a way it is retained, remembered and effectively interpreted by a medical student is considered to be a challenge which has resulted in crucial changes in the medical educational field, with a shift from didactic teacher centered and subject based teaching to the use of interactive, problem based, student centered learning. Learning styles and approaches of each medical undergraduate vary considerably and their learning needs also differ individually. The objective of the study was to assess the perception of 2nd year medical students towards teaching and learning methods, to know their preferences among 3 commonly used audio visual teaching methods chalk and board (CB), power point teaching (PPT) and over-head projector (OHP), to explore the most influencing qualities of a teacher perceived by these medical undergraduates. Methods: A cross-sectional descriptive questionnaire-based study was conducted among 2nd year medical students of AIMS, B. G. Nagar, Karnataka, India. A pre-designed, pre-tested self-administered questionnaire was used to collect data. Results: Total respondents were 184. Among them 116 were females (63.04%) and 68 were males (36.95%). All were within the age group of 19-21 years. Chalk and board (64%) was the most preferred teaching method. 76.63% students felt that chalk board facilitates interaction between students and teacher, 69.56% perceived that diagrams can be easily copied, 67.39% opined that clinical problems can be solved better. However to demonstrate the clinical conditions (70.65%) and covering more subject per lecture (59.23%) students preferred ppt teaching. The preferred learning method in our study was small group discussion (29%) followed by tutorials (27%), self-study (23%) and lectures (16%). Approachability (54.89%) of a teacher towards students, good teaching skills (50.54%) and knowledge towards the subject (45.65%) are the most influencing qualities of a teacher perceived by these medical undergraduates. Conclusions: Chalk and board teaching remains the best preferred teaching aid which can be supplemented with PPT and OHP to improve medical teaching. Small group discussion is the most preferred learning method when compared with tutorial, student’s seminar and lectures indicating that students are more interested in active teaching and learning methods.